2019
DOI: 10.3390/su11102898
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability, Resilience and Population Ageing along Schengen’s Eastern Border

Abstract: Border and administrative divisions usually have considerable severe impacts on the economic growth and sustainable management of natural and human on both sides of the border. Schengen border regions mostly perform less well economically in comparison to non-border regions, and the citizens and businesses are facing all sorts of barriers on a day-to-day basis when crossing EU Schengen borders. Therefore, the research is focused on the resilience of the frontier areas of Slovakia and Ukraine, both experiencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Taking into consideration potential changes in water conditions, appropriate measures have to be undertaken in order to minimize the effects of climate change in the future. Numerous analyses showed that undertaking such measures related to reasonable management of water resources is a crucial issue in the case of many countries and in various climate zones [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Case Study and Datamentioning
confidence: 99%
“…Taking into consideration potential changes in water conditions, appropriate measures have to be undertaken in order to minimize the effects of climate change in the future. Numerous analyses showed that undertaking such measures related to reasonable management of water resources is a crucial issue in the case of many countries and in various climate zones [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Case Study and Datamentioning
confidence: 99%
“…It seems that the timely capture of the onset of the mentioned industrial revolution is, for particular industrially oriented countries, of essential significance, not only from the point of view of their competitiveness [1,2]. Globalization and risk factors arising therefrom (data safety, information sensitivity and vulnerability, readiness for crisis situations) will verify the effect of digitalization on the continuity of business management [3][4][5][6][7][8][9][10]. Furthermore, in Slovakia, which is industrially oriented, this issue is dealt with by numerous experts from practice, academicians, and often, unfortunately, by politicians too.…”
Section: Introductionmentioning
confidence: 99%
“…Socio-demographic capacity relies (beside other factors) on population ageing in a district and the health of its population because these factors influence the ability and the possibility to respond to external shocks [88] such as redundancies in the region, which will contribute to increasing unemployment. It is important to respect age diversity beside other factors when pursuing the dismissal and the need to provide outplacement.…”
Section: Discussionmentioning
confidence: 99%